2014
DOI: 10.1021/ie5036308
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Hierarchical ZSM-5 Zeolite and Its Performance in Catalyzing Methanol to Gasoline Conversion

Abstract: A simple method was developed and tested to synthesize hierarchical ZSM-5 zeolites using tetrapropylammonium hydroxide as a sole structure directing agent to generate intercrystalline mesopores. XRD analysis confirmed the formation of ZSM-5 zeolites. SEM and TEM imaging analyses revealed the presence of hierarchical structure, formed by self-assembly of highly crystalline, nanosized primary particles. Solid-state MAS NMR analysis showed the vast majority of Al atoms were tetrahedrally incorporated with Si atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 52 publications
(106 reference statements)
3
51
0
Order By: Relevance
“…The larger spices would be more likely to become trapped and thereby form a coke precursor. So, the solely microporous ZSM-5 catalyst is progressively deactivated as the micropores are filled with coke deposits, or their entrances become blocked [54]. In contrast, in the case of hierarchical structured zeolites (alkali-treated) with intra-and/or intercrystalline mesoporosity, coke is formed mainly on the external surface and/or mesopores.…”
Section: Catalystmentioning
confidence: 99%
“…The larger spices would be more likely to become trapped and thereby form a coke precursor. So, the solely microporous ZSM-5 catalyst is progressively deactivated as the micropores are filled with coke deposits, or their entrances become blocked [54]. In contrast, in the case of hierarchical structured zeolites (alkali-treated) with intra-and/or intercrystalline mesoporosity, coke is formed mainly on the external surface and/or mesopores.…”
Section: Catalystmentioning
confidence: 99%
“…Zeolites could be used more efficiently if the diffusion path length of the micropore could be reduced by synthesis of nanocrystals or by mesopore formation in larger zeolite crystals, improving transport of molecules to and from the active sites [4,8,10] . Numerous studies have been reported to synthesize hierarchical structured zeolites [11][12][13][14][15][16] , though these morphologies lead to lower crystallinity and more framework defects [17,18] . Framework defects are prone to coke formation, as several studies have demonstrated a direct correlation between coke formation and silanol defects [19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…The mesoporous ZSM-5 zeolites with improved diffusion efficiency and acids accessibility showed better performance than the conventional ZSM-5 zeolite. TPAOH, a conventional microporous template, can be used as the single SDA to prepare hierarchical ZSM-5 zeolite [75,76]. Hua et al [76] successfully prepared the hierarchical ZSM-5 zeolite using only TPAOH as the SDA through one-step hydrothermal process at a relatively low temperature of 100 • C, and they proposed a "nucleation/growth-demetallation/recrystallization" mechanism during the hydrothermal synthesis process.…”
Section: Single Templating Methodsmentioning
confidence: 99%